Users and information resources: An extension of the analytical model of collections and their catalogues into usage and transactions - Heaney, M (2005)
Michael Heaney of Oxford University Library Services has extended his entity-relation model of collections and their catalogues to include modelling of the means by which users obtain access to collections. The extended model introduces a number of additional entities and relationships, and enumerates some additional attributes for some of the entities that were present in the original model. The document also includes some illustrative examples of the transactions that occur between entities as users access collections.